Pengaruh Komitmen Organisasi, Gaya Kepemimpinan Demokratis, Etika Profesi dan Pengalaman Auditorpada Kinerja Auditor - Candra, I Wayan; Badera, Dewa Nyoman (E-Jurnal Akuntansi; Vol 21 No 2 (2017), 2017)
This study aims to examine the influence of organizational commitment, democratic leadership style, ethics and experience of auditors on auditor performance in public accounting firm in Bali. Profession of public accountants is responsible for raising the level of reliability of the company's financial statements.User of the audit report wishes that the audited financial statements by the public accountant are free from material misstatement, trustworthy to be used as the basis for decision making and are in conformity with accounting principles applicable in Indonesia. Therefore, an independent and objective professional service is required to assess the fairness of the financial statements presented by the management. This research was conducted at Public Accounting Firm in Bali area registered with Indonesian Institute of Certified Public Accountant (ICPA) in 2016. The population in this research is all auditors who work at Public Accounting Firm in Bali with the number of 80 auditors with the number of questionnaires returned 71 and sample used is 59 auditors. Data collection using survey method with questionnaire, while the method of determining the sample is the method of non probability sampling with purposive sampling technique. Analysis technique used is multiple linear regression. Results showed organizational commitment, democratic leadership style, professional ethics and auditor experience have a positive effect on auditor performance